Bollywood and Turkish Films in Antwerp (Belgium): Two Case Studies on Diasporic Distribution and Exhibition - Vandevelde, Iris; Smets, Kevin; Meers, Philippe; Vande Winkel, Roel; Van Bauwel, Sofie (Javnost-The Public, 2011)
This article, a contribution to the thriving scholarship on the engagements between homeland media and diasporic audiences, breaks new ground through a comparative, political economy inspired analysis of two case studies with transnational implications. First we describe the theatrical distribution and exhibition of homeland films towards/by their diasporas, focusing on Indian and Turkish film structures in one location, the Belgian city of Antwerp. Interviews with 45 key players, participant observation and complementary archival research allow us to reconstruct how privately organised film screenings were substituted by commercial initiatives. Further analysis exploring the relations between local exhibitors and transnational distributors evaluates these structures against the background of global media industries' developments in terms of power and transformations, such as increasing competition.